Pilots’ visual scan pattern and situation awareness in flight operations - Yu, Chung-San; Wang, Eric Min-yang; Li, Wen-Chin; Braithwaite, Graham (Aerospace Medical Association, 2014)
Introduction: Situation awareness (SA) is considered an essential prerequisite for safe flying. If the impact of visual scanning patterns on a pilot’s situation awareness could be identified in flight operations, then eye-tracking tools could be integrated with flight simulators to improve training efficiency. Method: Participating in this research were 18 qualified, mission-ready fighter pilots. The equipment included high-fidelity and fixed-base type flight simulators and mobile head-mounted eye-tracking devices to record a subject’s eye movements and SA while performing air-to-surface tasks. Results: There were significant differences in pilots’ percentage of fixation in three operating phases: preparation (M = 46.09, SD = 14.79), aiming (M = 24.24, SD = 11.03), and release and break-away (M = 33.98, SD = 14.46). Also, there were significant differences in pilots’ pupil sizes, which were largest in the aiming phase (M = 27,621, SD = 6390.8), followed by release and break-away (M = 27,173, SD = 5830.46), then preparation (M = 25,710, SD = 6078.79), which was the smallest. Furthermore, pilots with better SA performance showed lower perceived workload (M = 30.60, SD = 17.86), and pilots with poor SA performance showed higher perceived workload (M = 60.77, SD = 12.72). Pilots’ percentage of fixation and average fixation duration among five different areas of interest showed significant differences as well. Discussion: Eye-tracking devices can aid in capturing pilots’ visual scan patterns and SA performance, unlike traditional flight simulators. Therefore, integrating eye-tracking devices into the simulator may be a useful method for promoting SA training in flight operations, and can provide in-depth understanding of the mechanism of visual scan patterns and information processing to improve training effectiveness in aviation.
Keywords: attention allocation; aviation safety; fixation duration; training evaluation